The hemodynamic management of 5177 neurosurgical and orthopedic patients who underwent surgery in the sitting or "beach chair" Position without incidence of adverse neurologic events - Pin-On P. (2014)
Background: A small number of highly publicized case reports describe ischemic brain or spinal cord injury after surgery in the sitting ("beach chair") position. The incidence of such catastrophic outcomes remains unknown, as does the relationship between arterial blood pressure management and injury, because few hemodynamic details were included with those 4 cases. To add quantitative data to the discussion of anesthesia in the sitting position, we examined the detailed hemodynamics of a large number of patients managed at our institution who sustained no similar catastrophic outcomes. Methods: A comprehensive, retrospective, interrogation was performed of the electronic hemodynamic record for all 5177 patients who underwent either orthopedic shoulder surgery or neurological surgery in the sitting position at Mayo Clinic Rochester between January 1, 2002 and December 31, 2009. RESULTS: No immediate postoperative catastrophic outcomes occurred in 5177 sitting patients undergoing surgery and general anesthesia in the sitting position. For orthopedic shoulder surgery patients, intraoperative systolic blood pressures obtained from an arterial line referenced to heart level decreased 14.4% ± 12.7% (mean ± SD), and those obtained from a noninvasive blood pressure (NIBP) cuff referenced to heart level decreased 19.3% ± 12.6%. For neurosurgical patients, the average reductions in intraoperative mean arterial blood pressures from baseline were 17.6% ± 11.5% and 19.7% ± 10.7% for patients with heart- and head-level transducer placement, respectively. The absolute intraoperative mean arterial blood pressures (mean ± SD) for orthopedic patients measured by NIBP referenced to heart level were 75 ± 8 mm Hg; for orthopedic patients measured from an arterial line referenced to heart level were 74 ± 7 mm Hg; for neurosurgical patients measured with an arterial line referenced to heart level were 78 ± 7 mm Hg; and for neurosurgical patients measured with an arterial line referenced to head level were 75 ± 7 mm Hg. Over the entire duration of surgery, 52% (95% confidence interval [CI], 49%-56%) of neurosurgical patients, 51% (95% CI, 47%-55%) of orthopedic patients monitored with an A-line, and 48% (95% CI, 46%-50%) of orthopedic patients monitored with NIBP experienced ≥1 episodes of systolic blood pressure reduction >40% below baseline. CONCLUSION: This study provides a descriptive summary of intraoperative blood pressure changes, measured either invasively or noninvasively, and referenced to either head or heart level, but never lower than heart level, in patients under general anesthesia in the sitting position who sustained no catastrophic outcomes. © 2013 International Anesthesia Research Society.